Scaling the changes in lifestyle, attitude, and behavioral patterns among COVID-19 vaccinated people: insights from Bangladesh. Issue 1 (31st January 2022) - Hossain, Md. Emran; Islam, Md. Sayemul; Rana, Md. Jaber; Amin, Md. Ruhul; Rokonuzzaman, Mohammed; Chakrobortty, Sudipto; Saha, Sourav Mohan
ABSTRACT: With the advent of COVID-19 vaccines, countries around the globe are anticipating a way out from the pandemic. Despite being an initiative to contain the COVID-19 virus spreading, the mass vaccination program also raised concerns about its consequences on the lifestyle, attitude, and behavioral pattern of vaccinated people in the post-vaccination period. With this in mind, this study investigated changes in lifestyle, attitude, and behavior among vaccinated people in Bangladesh. A cross-sectional survey was conducted incorporating 1227 COVID-19 vaccinated respondents from eight divisions of Bangladesh. The relative importance index (RII) was used to assess the most compelling lifestyle, attitude, and behavior changes, while binary logistic regression was used to identify factors driving the changes. Findings disclosed that respondents increased the physical contact with non-vaccinated ones and amplified consuming nutritious food after vaccination. The inclination of avoiding distance, handshaking, abandoning sanitizer and mask, visiting crowded places, traveling, and staying outside longer was found to be increased among vaccinated individuals. Surprisingly, about seven out of ten surveyed respondents exhibited a sedentary lifestyle, while 67.37% of respondents showed negative behavioral changes following the vaccination period. A positive attitude was observed in encouraging others to be vaccinated against COVID-19. However, 92% of the respondents positively changed their attitude toward the COVID-19 vaccine after vaccination. Furthermore, the participants' age, residence, economic status, and educational level influenced lifestyle, attitude, and behavioral changes positively. The study recommends informing citizens about the opacity of vaccinations' ability to contain infections and encouraging them to continue following COVID-19 protective guidelines.